Hysteroscopy in one hundred cases of postmenopausal uterine bleeding, in the detection of uterine cancer and atypical endometrial hyperplasia - Devabhaktuni, Pratibha; Allani, Padmaja; Komatlapalli, Suneetha; Ksheerasagara, Rekha Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Evaluation was done in 100 women presenting with postmenopausal bleeding, (PMB), to discuss the utility of hysteroscopy combined guided endometrial curettage in the diagnosis of uterine cancer and endometrial hyperplasia, and, treat benign lesions, like polyps, synechiae at the same sitting. At MGMH during the years, 2002 to 2006, there were 57 women, and at care, 40 women with PMB during 2011 to 2013, and three in a nursing home, Hyderabad, were investigated. Methods: Evaluation was done in 100 women presenting with PMB by hysteroscopy and curettage to diagnose the cause of PMB and benign lesions like polyps, synechiae were managed by operative hysteroscopy. Bettocchi 5 mm hysteroscope, monopolar instruments and glycine was used for excision of polyps. Results: In one hundred women with PMB, 19% had cancer. Endometrial adenocarcinoma in 14, endocervical carcinoma in 2, uterine carcinosarcoma in 3 cases. All 3 cases of uterine carcinosarcoma on hysteroscopy were large polyps measuring 5×5-6 cm size. Atypical hyperplasia endometrium in 7% and simple hyperplasia in 17%, was reported on histopathology, in cases with hyperplastic endometrium on hysteroscopy. Benign polyps in 41% were managed at the same sitting by operative hysteroscopy. Conclusions: Women with postmenopausal bleeding must have USG, trans vaginal sonography (TVS), endometrial thickness (ET) measurement, preferably endometrial echo complex (EEC). In women with PMB, the risk of uterine cancer would be 19%, i.e., 1 out of 5 women. Atypical hyperplasia in 7%. Hysteroscopy guided curettage, with histopathology, is the gold standard protocol in cases of PMB.